Simplifying (c + 3) + -2c + -1(1 + -3c) = 2 Reorder the terms: (3 + c) + -2c + -1(1 + -3c) = 2 Remove parenthesis around (3 + c) 3 + c + -2c + -1(1 + -3c) = 2 3 + c + -2c + (1 * -1 + -3c * -1) = 2 3 + c + -2c + (-1 + 3c) = 2 Reorder the terms: 3 + -1 + c + -2c + 3c = 2 Combine like terms: 3 + -1 = 2 2 + c + -2c + 3c = 2 Combine like terms: c + -2c = -1c 2 + -1c + 3c = 2 Combine like terms: -1c + 3c = 2c 2 + 2c = 2 Add '-2' to each side of the equation. 2 + -2 + 2c = 2 + -2 Combine like terms: 2 + -2 = 0 0 + 2c = 2 + -2 2c = 2 + -2 Combine like terms: 2 + -2 = 0 2c = 0 Solving 2c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '2'. c = 0 Simplifying answer c = 0